HUBUNGAN PERILAKU KELUARGA SADAR GIZI DENGAN KEJADIAN STUNTING PADA BALITA DI KECAMATAN SORKAM DESA AEK RASO KABUPATEN TAPANULI TENGAH TAHUN 2016 - Simatupang, Meiyati (Yayasan Akrab Pekanbaru, 2018)
This study aims to determine the relationship of family awareness of nutrition behavior with the occurrence of Stuting in children under five in Sorkam District, Aek Raso Village, Tapanuli Tengah Regency, 2016. The results showed that the majority of respondents had nutritional conscious behavior as many as 71 people (65.1%), the majority of respondents did not experience stunting (normal) as many as 106 people (97.2%). As a conclusion from this study, there is a correlation between the behavior of the family aware of nutrition and the occurrence of Stunting in children under five where from the Chi Square test results obtained X2 count of 5.764> X2 tables of 3.841. It is recommended that respondents pay attention to nutritional awareness (routine weighing of toddlers at the posyandu, application of exclusive breastfeeding, varied eating, use of iodized salt, and nutritional supplements to children under five) so that there are no nutritional problems in the form of stunting.